The predictive value of serum LXA4, MK and CXCL16 for renal damage in children with allergic purpura: Serum LXA4, MK and CXCL16 for renal damage in allergic purpura - Xia, Ziwei; Cheng, Zhenfeng; Yuan, Xingrun; Xing, Shasha (Journal of Medical Biochemistry, 2025)
Objective To explore the predictive value of the combined application of serum intermediate factor (MK), lipoxin A4(LXA4), and CXC chemokine ligand 16(CXCL16) for renal damage in children with henoch-Schonlein purpura (HSP). Methods 117 children with HSP who were admitted to our hospital between January 2021 and December 2024 were selected for the HSP group. After treatment, they were followed up for 6 months, and the occurrence of renal damage was statistically analyzed. The control group consisted of an additional 59 voluntarily enrolled youngsters who received health examinations throughout the same time frame. The levels of serum MK, LXA4, and CXCL16 in the two groups of research patients were determined using an enzyme-linked immunosorbent assay, and clinical data from children with HSP were gathered. The factors that contribute to renal damage in children with HSP were investigated using both univariate and multivariate logistic regression. Serum MK, LXA4, and CXCL16 levels were analyzed for their predictive value of renal impairment in children with HSP using a receiver operating characteristic (ROC) curve. Results Compared with the control group, the levels of serum MK, LXA4 and CXCL16 in the HSP group were all increased (P<0.05). During the 6-month follow-up, among the 117 children with HSP, 35 cases developed renal damage (renal damage group), with an incidence rate of 29.91%(35/117), and the remaining 82 cases were in the non-renal damage group. The proportions of children with a diagnosis time of ≥7 days, respiratory tract infections, and serum levels of MK, LXA4, and CXCL16 in the renal damage group were all higher than those in the non-renal damage group (P<0.05). However, the percentages of children with joint pain/arthritis, gastrointestinal bleeding, and EBV infection did not change statistically significantly between the two groups in terms of gender, age, or body weight (P>0.05). According to multivariate logistic regression analysis, a diagnosis time of at least seven days, respiratory tract infection, and elevated levels of serum MK, LXA4, and CXCL16 were all independent risk factors for renal damage in children with HSP (P<0.05). The results of ROC curve analysis showed that the area under the curve for the combined prediction of serum MK, LXA4, and CXCL16 levels for renal damage in children with HSP was larger than that predicted by MK, LXA4, and CXCL16 alone (P<0.05). Conclusion The elevated levels of serum MK, LXA4 and CXCL16 in children with HSP are closely related to renal damage. The combined prediction of serum MK, LXA4 and CXCL16 levels in children with HSP has a relatively high value.